OVERCOMING GRAMMATICAL AND LEXICAL BARRIERS IN REAL COMMUNICATION: A PRACTICAL APPROACH - Yuldasheva Mahliyo Akramjon kizi (American Journals, 2025)
This article analyzes practical approaches to overcoming grammatical and lexical barriers that arise during real communication. Based on literature review, the types of communication barriers, their causes, and methods of elimination are studied. The article provides practical recommendations for language learners and teachers, focusing on strategies that can be implemented in real-world communication scenarios without relying on experimental studies or interventions.
Keywords: Communication barriers, grammatical barriers, lexical barriers, communicative competence, practical approach, language acquisition, real-world communication.